A method for characterizing the degree of fusion between new and old asphalt based on fluorescence microscopy

Through the method based on fluorescence microslicing, the degree of fusion between new and old bitumen is accurately observed and quantified, and the problem of difficult to accurately determine the degree of fusion in the prior art is solved, and the accuracy of the design and performance evaluation of regenerated bitumen mixtures is improved.

CN115684109BActive Publication Date: 2025-04-29SOUTH CHINA UNIV OF TECH +4

Patent Information

Application Number
CN202211311043.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-25
Publication Date
2025-04-29
Estimated Expiration
2042-10-25

AI Technical Summary

Technical Problem

It is difficult for the prior art to accurately observe and quantify the degree of fusion between new and old asphalt in regenerated asphalt mixtures, resulting in large errors in the mix design and performance evaluation.

Method used

Using a fluorescence microscope-based method, SBS modified asphalt on the wooden simulated aggregate surface was observed through a confocal microscope, multiple fluorescence images of new and old asphalt were output, noise reduction and fluorescence intensity analysis were performed, and the ratio of the number of new and old asphalts was calculated to determine the degree of fusion.

Benefits of technology

The accuracy of the degree of fusion of new and old asphalt is achieved, and the accuracy of the design of recycled asphalt mixture and the evaluation accuracy of the performance of the mixture are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115684109B_ABST
    Figure CN115684109B_ABST
Patent Text Reader

Abstract

The invention discloses a method for characterizing the degree of fusion of new and old asphalt based on fluorescence microscopy, and the process is as follows: using a confocal microscope to observe the surface of a wood simulated aggregate coated with homogenous SBS modified asphalt, obtaining fluorescence images at different depths, calculating an average fluorescence intensity curve, and fitting a fluorescence intensity attenuation correction function; observing the mixed asphalt on the surface of the wood simulated aggregate under the confocal microscope; scanning from the outermost layer to the innermost layer of the wood simulated aggregate, and outputting a plurality of fluorescence images of the new and old asphalt in the asphalt film thickness layer; performing noise reduction processing on the fluorescence image, obtaining a concentration change curve of the new asphalt and correcting it using an attenuation correction function; calculating a concentration attenuation change curve of the new asphalt, judging the influence of noise and the asphalt fusion layer, retaining the layer position with a fitting coefficient less than or equal to 95%, and calculating the concentration attenuation change curve after removing the influence of noise and fluorescence signal attenuation; and defining the degree of fusion of the mixed asphalt by an area method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road engineering, and in particular to a method for characterizing the degree of fusion of new and old asphalt based on fluorescent microscopy. Background Art

[0002] Today, the transportation industry is in urgent need of transformation, from high-speed development to high-quality development and green development. Therefore, asphalt pavement recycling has gradually become a hot area in the highway industry. Through asphalt pavement recycling technology, the recycled asphalt pavement materials of waste ordinary asphalt are treated with new aggregates and new asphalt with good performance through special processes to obtain asphalt mixtures that can be put back into highway use, which not only solves the problem of resource shortage in development, but also conforms to the development trend of sustainable development.

[0003] The fusion of new and old asphalt is the core step of asphalt regeneration. In the past, researchers have obtained a large number of regeneration research results through laboratory experiments, such as mixture regeneration theory and design calculation methods. However, these experiments are based on the theory that new asphalt and old asphalt are fully integrated. In fact, the two will not immediately and completely integrate, which leads to large errors in the calculation of the amount of new asphalt added and the evaluation of the performance of the later mixture during the design of the recycled mixture. Using accurate observation methods to determine the degree of integration of new and old asphalt in asphalt mixtures and accurately guide the regeneration of asphalt mixtures is of great significance to the development of recycling technology and the improvement of the quality of recycled asphalt roads.

[0004] In addition, the current observation and characterization methods for the fusion of new and old asphalt include performance parameter method, component analysis method, microscope observation method, and coincidence characterization method. Among them, only the microscope observation method can directly and truly observe the fusion state of new and old asphalt, and the other methods are to deduce the fusion state through testing or changes in the properties of asphalt. Therefore, it is necessary to develop a more accurate characterization method for the fusion of new and old asphalt based on a microscope. Summary of the invention

[0005] The purpose of the present invention is to solve the above-mentioned defects in the prior art and provide a method for characterizing the degree of fusion of new and old asphalt based on fluorescent microscopy. The observation and characterization method provided by the present invention can truly observe the distribution of new and old asphalt and accurately quantify the degree of fusion of new and old asphalt on recycled asphalt mixture.

[0006] The purpose of the present invention can be achieved by adopting the following technical solutions:

[0007] A method for characterizing the degree of fusion of new and old asphalt based on fluorescence microscopy, the method comprising the following steps:

[0008] S1. All wood simulated aggregates are taken out from the recycled asphalt mixture and placed on a glass slide. The surface of the wood simulated aggregate is coated with homogeneous SBS modified asphalt. The SBS modified asphalt on the surface of the wood simulated aggregate is observed under a confocal microscope, wherein the surface of the wood simulated aggregate is sequentially provided with an innermost layer of asphalt film, a thickness layer of asphalt film, and a surface layer of asphalt film from inside to outside;

[0009] S2. Set the magnification of the microscope and adjust the position so that the mixed asphalt on the surface of the wood simulated aggregate covers the entire microscope window. Start from the surface layer of the asphalt film and scan toward the innermost layer of the asphalt film. Scan to cover the entire thickness layer depth of the asphalt film. Set the scanning layer depth interval and output n+1 new and old asphalt fluorescence images, which are recorded as the i=0, 1, 2, ..., nth layer fluorescence images respectively. When i=0, it corresponds to the surface layer of the asphalt film, and when i=n, ​​it corresponds to the innermost layer of the asphalt film. The i=0, 1, 2, ..., nth layer fluorescence images correspond to the fluorescence images of different layers respectively.

[0010] S3, performing noise reduction processing on the fluorescence image, calculating the average fluorescence intensity of each fluorescence image and arranging them from the outside to the inside according to the scanning depth of the asphalt film of each fluorescence image, the depth layer corresponding to the i=0th layer of fluorescence image is 0um, and the depth of each layer of fluorescence image is defined in turn according to the scanning depth interval;

[0011] S4, the position of the depth layer of 0um is taken as SBS modified asphalt, which is also called new asphalt, and the fluorescence intensity of the fluorescence image of the i=0th layer is regarded as the new asphalt concentration of 1, and the fluorescence intensity of the fluorescence image of the i=1, 2, ..., nth layer is normalized in turn to obtain the average fluorescence intensity curve in the normalized asphalt film thickness layer, which is recorded as the first average fluorescence intensity curve;

[0012] S5. Conduct a set of control experiments to observe the homogeneous SBS modified asphalt evenly applied on the surface of the wood aggregate. After comparison, the attenuation of the fluorescence intensity signal at each layer depth can be obtained, and the attenuation correction function can be calculated;

[0013] S6. Calculate the fluorescence intensity concentration attenuation change curve of the new asphalt using the second average fluorescence intensity curve, determine the influence of noise and the asphalt fusion layer, retain the layer with a fitting coefficient μ less than or equal to 95%, and calculate the fluorescence intensity concentration attenuation change curve after removing the influence of noise and fluorescence signal attenuation, correct the retained fluorescence curve using the attenuation correction function, reduce the influence of signal attenuation, and obtain the second average fluorescence intensity curve;

[0014] S7. Analyze the second average fluorescence intensity curve to obtain the distribution diagram of new and old asphalt. Analyze the fluorescence intensity concentration attenuation change curve (second average fluorescence intensity curve) after removing the noise and fluorescence signal attenuation by the area method to obtain the ratio of the number of new and old asphalt in the asphalt film thickness layer. Calculate the degree of fusion of the new and old asphalt based on the ratio of the number.

[0015] Furthermore, the calculation formula of the attenuation function in step S5 is as follows:

[0016]

[0017]

[0018] Where: i represents the number of image layers distributed along the depth direction; k i represents the fluorescence intensity enhancement factor of the i-th layer image; represents the maximum fluorescence intensity of the i-th layer image after correction; x i represents the maximum fluorescence intensity of the i-th layer image; x max represents the maximum value of fluorescence intensity in all depth images; d i -d max represents the distance from the i-th image to the maximum fluorescence image along the depth direction;

[0019] When the excitation light of the confocal microscope penetrates the sample, the sample will absorb and refract the excitation light, reducing the intensity of the excitation light penetrating deep into the tissue. The attenuation of the signal will hinder the microscope from extracting information from the data, and the fluorescence intensity of the image will gradually decay as the depth of the scan increases. In this experiment, the new asphalt is SBS modified asphalt, and the old asphalt is aged matrix asphalt. Both are asphalt materials with similar refractive index and absorption rate, and have basically the same effect on signal attenuation. Therefore, the intensity attenuation function can be designed to fit the test and correct the attenuation of the test signal. The maximum fluorescence intensity of each layer of the homogeneous SBS modified asphalt evenly applied on the surface of the wood aggregate is analyzed. When i=0, the fluorescence signal has no attenuation, and the maximum fluorescence intensity of this layer is the ideal case. When i=1,2,,,n, the fluorescence signal attenuation will increase with the increase of the layer. The attenuation function can be obtained by comparing with the maximum fluorescence intensity when i=0. The correction of the attenuation function can avoid the interference of signal attenuation on the accuracy of the experiment.

[0020] Furthermore, the calculation formula of the fitting coefficient μ in step S6 is as follows:

[0021]

[0022] In the formula, ρ i represents the fluorescence intensity of the i-th layer fluorescence image, ρ maxrepresents the maximum value of the average fluorescence intensity in different layers of the entire asphalt film thickness layer, ρ min It represents the minimum value of the average fluorescence intensity in different layers of the entire asphalt film thickness layer.

[0023] Furthermore, the formula of the fluorescence intensity ρ′ after removing the influence of noise and fluorescence signal attenuation in step S6 is as follows:

[0024]

[0025] In the formula, ρ′ represents the corrected fluorescence intensity, k is the fluorescence signal attenuation correction coefficient, ρ 噪声 It represents the fluorescence intensity generated by noise, which is the fluorescence intensity of the layer where the SBS modified asphalt stops longitudinal diffusion. max() means taking the maximum value from all the results in the brackets.

[0026] The data information of fluorescence images will be affected by signal attenuation and noise. By removing the influence of noise and signal attenuation through formula (4), the accuracy of the data can be improved.

[0027] Furthermore, the second average fluorescence curve analysis in step S7 is as follows:

[0028] In the fusion of new and old asphalt, SBS modified asphalt gradually began to diffuse into the aged asphalt layer, but the deeper it went into the aged asphalt layer, the less SBS modified asphalt existed. In the fluorescence image obtained through the experiment, the fluorescence intensity is the fluorescence effect of SBS modified asphalt. The fluorescence intensity curve generated after the image fluorescence intensity processing can represent the concentration of new asphalt in different layers. The phenomenon that the amount of SBS modified asphalt gradually decreases with the increase of longitudinal depth during fusion can be represented by the continuously decreasing SBS modified asphalt concentration curve.

[0029] Furthermore, the calculation method of the fusion degree of the new and old asphalt in step S7 is as follows:

[0030] According to the usage ratio of new and old asphalt, that is, the number of old asphalt parts corresponding to 1 part of new asphalt during fusion, the entire asphalt film thickness layer is regarded as the fusion layer, and the degree of fusion of new and old asphalt DOB is calculated. * , the calculation formula is as follows,

[0031]

[0032] Where: min(,) means taking the smallest value of the elements in brackets, S virgin represents the amount of new asphalt involved in fusion, S reclaimed Indicates the amount of old asphalt involved in fusion, C virgin Indicates the proportion of new asphalt added to the total amount of asphalt.

[0033] Traditionally, the industry defines the degree of fusion as the contribution of old asphalt and regeneration agent to the conventional and rheological properties of the final mixed asphalt, which can be expressed as the ratio of activated old asphalt to total old asphalt. However, in reality, fusion is a phenomenon caused by the participation of both new asphalt and old asphalt. Using a single factor to analyze fusion cannot reflect the overall situation. * The indicator makes up for the shortcomings of the traditional definition and defines the degree of fusion by the distribution of new and old asphalt in the entire fusion layer. This indicator can more accurately define the amount and degree of fusion of new and old asphalt.

[0034] Furthermore, the calculation method of the fusion degree of the new and old asphalt in step S7 is as follows:

[0035] According to the usage ratio of new and old asphalt, that is, the number of old asphalt parts corresponding to 1 part of new asphalt during fusion is fused, each layer of different depth is regarded as a fusion layer, and the degree of fusion of new and old asphalt in each layer of different depth is calculated. Then, the overall degree of fusion of new and old asphalt DOB is obtained by integrating the thickness of the entire asphalt film. The calculation formula is as follows:

[0036]

[0037]

[0038]

[0039] In the formula, S virgin-i represents the new asphalt amount at the depth layer corresponding to the i=0th layer of fluorescence image, S reclaimed-i represents the amount of old asphalt in the depth layer corresponding to the i=0th layer of fluorescence image, C v-r represents the ratio of new and old asphalt, min(,) represents the smallest value of the elements in brackets, S virgin represents the amount of new asphalt involved in fusion, S reclaimed Indicates the amount of old asphalt involved in fusion, C virgin It indicates the proportion of new asphalt added to the total asphalt, W Rap;active Indicates the amount of old asphalt mobilized during the mixing process, W Rap;total Represents the total amount of old asphalt, RAP active,% It indicates the amount of active recycled asphalt mobilized during the mixing process, taken as 100%.

[0040] The diffusion fusion of new and old asphalt occurs at any point where two fusion layers come into contact, that is, at each depth layer, DOB *The indicator calculates the degree of fusion based on the entire fusion layer, which has obvious errors. Therefore, the indicator needs to be improved on this basis, and the degree of fusion is calculated based on the unit depth layer (i.e., i = 0, 1, 2, ..., n) as the fusion layer, and then the entire fusion layer (the entire asphalt film thickness layer) is integrated to obtain the overall degree of fusion. The indicator obtained by this method is more accurate.

[0041] Compared with the prior art, the present invention has the following advantages and effects:

[0042] 1. One of the main difficulties in measuring the degree of fusion of new and old asphalt is that it is impossible to accurately determine the amount of new and old asphalt involved in the fusion. The present invention adopts an advanced laser confocal microscope as an observation instrument, which can intuitively and accurately observe the distribution of new and old asphalt in the asphalt film thickness layer on the recycled asphalt mixture, and provide accurate basic data for the analysis of the degree of fusion of new and old asphalt.

[0043] 2. The present invention uses fluorescent image processing technology to accurately quantify the amount of new and old asphalt involved in the fusion layer, and uses the quadratic integration method to establish a mathematical model to accurately quantify the degree of fusion in the new and old asphalt fusion layer on the recycled asphalt mixture. The model takes into account the participation of new asphalt in the fusion, and the degree of fusion obtained is closer to the actual situation.

[0044] 3. The present invention can be used to improve the design method of recycled asphalt mixture, guide actual engineering, and evaluate the quality of the recycled asphalt mixture shipped out of the factory by the degree of fusion. At the same time, the fusion of new and old asphalt is a long process, and the present invention provides a basic method for observing the long-term fusion effect of recycled asphalt mixture. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0046] Figure 1 is a schematic diagram of observing the wood simulated aggregate under a microscope in an embodiment of the present invention;

[0047] Figure 2 is a schematic diagram of a fluorescent image obtained by scanning the thickness layer of an asphalt film with a microscope in an embodiment of the present invention;

[0048] Figure 3 is a schematic diagram of a fluorescence intensity curve of mixed asphalt and a fluorescence signal in an embodiment of the present invention;

[0049] Figure 4 is a schematic diagram of the attenuation rate in an embodiment of the present invention;

[0050] Figure 5is a distribution diagram of new and old asphalt in an embodiment of the present invention;

[0051] Figure 6 Schematic diagram of the fluorescence intensity curve of new asphalt on new and old aggregates in an embodiment of the present invention;

[0052] Figure 7 It is a schematic diagram of a group of 0-20um fluorescence scanning in an embodiment of the present invention. DETAILED DESCRIPTION

[0053] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] Example 1

[0055] This embodiment discloses a method for characterizing the degree of fusion of new and old asphalt based on fluorescence microscopy, and the method for characterizing the degree of fusion of new and old asphalt includes the following steps:

[0056] S1. Take all the wood simulated aggregates out of the recycled asphalt mixture and place them on a glass slide. Apply homogeneous SBS modified asphalt on the surface of the wood simulated aggregates. Observe the SBS modified asphalt on the surface of the wood simulated aggregates under a confocal microscope. Figure 1 As shown, the thickness layer of the asphalt film wrapped on the surface of the wood simulated aggregate is observed by confocal laser microscopy, and the scan is from the surface layer to the innermost layer. The new and old asphalt are fused in the asphalt film thickness layer, and the laser confocal scanning can observe the location where the new and old asphalt are fused. Among them, the innermost layer of the asphalt film, the asphalt film thickness layer, and the asphalt film surface layer are arranged in sequence from the inside to the outside on the surface of the wood simulated aggregate;

[0057] S2. Set the magnification of the microscope and adjust the position so that the mixed asphalt on the surface of the wood simulated aggregate covers the entire microscope window. Start from the surface layer of the asphalt film and scan toward the innermost layer of the asphalt film. The scan covers the entire thickness layer depth of the asphalt film. Set the scanning layer depth interval and output n+1 new and old asphalt fluorescence images, which are recorded as the i=0, 1, 2, ..., nth layer fluorescence images respectively. When i=0, it corresponds to the surface layer of the asphalt film, and when i=n, ​​it corresponds to the innermost layer of the asphalt film. The i=0, 1, 2, ..., nth layer fluorescence images correspond to the fluorescence images of different layers respectively. Figure 2 As shown, by setting the scanning interval, the asphalt film thickness layer can be scanned from the surface layer to the innermost layer in sequence to obtain n+1 fluorescence images, and the fluorescence images of the 0th layer, 1st layer... ith layer... nth layer depth layers are defined in sequence according to the scanning depth position.

[0058] S3, performing noise reduction processing on the fluorescence image, calculating the average fluorescence intensity of each fluorescence image and arranging them from the outside to the inside according to the scanning depth of the asphalt film of each fluorescence image, the depth layer corresponding to the i=0th layer of fluorescence image is 0um, and the depth of each layer of fluorescence image is defined in turn according to the scanning depth interval;

[0059] S4, the position of the depth layer of 0um is taken as SBS modified asphalt, which is also called new asphalt, and the fluorescence intensity of the fluorescence image of the i=0th layer is regarded as the new asphalt concentration of 1, and the fluorescence intensity of the fluorescence image of the i=1, 2, ..., nth layer is normalized in turn to obtain the average fluorescence intensity curve in the normalized asphalt film thickness layer, which is recorded as the first average fluorescence intensity curve;

[0060] Figure 3 The fluorescence intensity curves of mixed asphalt and fluorescence signal are shown in the figure. The fluorescence intensity of mixed asphalt decreases with the increase of layer cutting depth, which is caused by the attenuation of fluorescence signal and the diffusion of new asphalt. The fluorescence intensity of mixed asphalt attenuates significantly at 0-12um, but the fluorescence signal does not attenuate significantly, indicating that the fluorescence intensity change in this depth range is mainly caused by the diffusion of new asphalt; and after 12um, the fluorescence intensity of mixed asphalt tends to be flat and basically does not change, while the fluorescence signal attenuates sharply, which does not conform to the normal attenuation law, indicating that there is basically no SBS modified asphalt after 12um, that is, there is no fluorescence intensity generated by SBS polymer, and the fluorescence intensity mainly comes from noise.

[0061] S5. Conduct a group of control experiments, evenly apply homogeneous SBS modified asphalt on the surface of wooden aggregate, repeat steps S2-S3, obtain scanning images of layers 0 to n through confocal microscopy scanning and processing, and obtain corresponding fluorescence intensities, which are recorded as the average fluorescence intensity curve of the control group. By comparing the maximum fluorescence intensity of the fluorescence image of layer i=0 (ideal situation) with the maximum fluorescence intensity of the fluorescence image of layer i=1, 2, ..., n in the asphalt film thickness layer (actual situation), the attenuation of the fluorescence intensity signal at each layer depth is obtained, and the attenuation correction function is calculated; specifically, Figure 7 shown.

[0062] The calculation formula of the attenuation function is as follows:

[0063]

[0064]

[0065] Where: i represents the number of image layers distributed along the depth direction; k i represents the fluorescence intensity enhancement factor of the i-th layer image; represents the maximum fluorescence intensity of the i-th layer image after correction; x i represents the maximum fluorescence intensity of the i-th layer image; x max represents the maximum value of fluorescence intensity in all depth images; d i -d max represents the distance from the i-th image to the maximum fluorescence image along the depth direction;

[0066] The fluorescence intensity of mixed asphalt decreases with the increase of layer cutting depth, which is caused by the attenuation of fluorescence signal and the diffusion of new asphalt. A preliminary analysis of the fluorescence signal intensity curve of a group of sample tests shows that the fluorescence intensity of mixed asphalt attenuates significantly at 0-12um, but the fluorescence signal does not attenuate significantly, indicating that the fluorescence intensity change in this depth range is mainly caused by the diffusion of new asphalt; and after 12um, the fluorescence intensity of mixed asphalt tends to be flat and basically does not change, while the fluorescence signal attenuates sharply, which does not conform to the normal attenuation law, indicating that there is basically no SBS modified asphalt after 12um, that is, there is no fluorescence intensity generated by SBS polymer, and the fluorescence intensity mainly comes from noise. At the same time, there is a clear boundary in the attenuation rate, and the attenuation rate in the depth range of 0-10.4um and 10.4-20um is not of the same order of magnitude. The fitting coefficient μ index is established to calibrate the position of the boundary. The results show that when μ>95%, the fluorescence intensity attenuation rate is small and the fluctuation is small. It can be considered that there is no SBS in these layers, and their fluorescence intensity comes from noise. Therefore, data with μ>95% are not included in the calculation to avoid noise interference on the test accuracy.

[0067] S6. Calculate the fluorescence intensity concentration attenuation change curve of the new asphalt using the second average fluorescence intensity curve, determine the influence of noise and the asphalt fusion layer, retain the layer with a fitting coefficient μ less than or equal to 95%, and calculate the fluorescence intensity concentration attenuation change curve after removing the influence of noise and fluorescence signal attenuation, correct the retained fluorescence curve using the attenuation correction function, reduce the influence of signal attenuation, and obtain the second average fluorescence intensity curve;

[0068] like Figure 4 As shown in the figure, there is a clear boundary between the decay rates, and the decay rates in the 0-10.4um depth layer and the 10.4-20um depth layer are not of the same order of magnitude. The fluorescence intensity decay rate in the 10.4-20um depth layer is small and has small fluctuations. It can be considered that SBS no longer exists in these layers, and their fluorescence intensity comes from noise.

[0069] S7. Analyze the second average fluorescence intensity curve to obtain the distribution diagram of new and old asphalt. Analyze the fluorescence intensity concentration attenuation change curve (second average fluorescence intensity curve) after removing the noise and fluorescence signal attenuation by the area method to obtain the ratio of the number of new and old asphalt in the asphalt film thickness layer. Calculate the degree of fusion of the new and old asphalt based on the ratio of the number.

[0070] Example 2

[0071] In this embodiment, the recycled asphalt asphalt mixture of wood simulated aggregate includes the following components in parts by weight: 1 part of wood block, 2 parts of sandpaper, 1 part of liquid reagent, and 100 parts of water.

[0072] In this embodiment, the stone aggregate is limestone. The wood simulation aggregate is a small regular tetrahedral wood block that has been processed, and the surface has a rough structure and good adhesion, and there is no fluorescent reaction under a fluorescence microscope. SBS modified asphalt has a fluorescent effect under a fluorescence microscope and plays the role of new asphalt in the recycled asphalt mixture. The asphalt film thickness of the recycled asphalt mixture is designed to be 20um. The RAP addition amount of the recycled asphalt mixture is designed to be 50%, and the ratio of new and old asphalt is 1:1.

[0073] The method for preparing asphalt mixture wood simulated aggregate in this embodiment comprises the following steps:

[0074] 110 parts of base asphalt, 40 parts of wood simulated aggregate and 1960 parts of limestone aggregate were mixed and preheated at 135℃ for 3 hours, and then the three were mixed at 165℃ to make an asphalt mixture. The asphalt mixture was evenly spread in a container, and then placed in a blast oven at about 135℃±3℃ for 4h±5min, and the asphalt mixture was turned over once every hour. After the asphalt mixture was cooled for 16 hours, the asphalt mixture after short-term aging was placed in an 85℃ blast oven for 120h±0.5h, and cooled to room temperature for 16 hours to obtain artificial RAP containing wood simulated aggregate. Subsequently, the artificial RAP was preheated at 120℃ for 3 hours, 1960 parts of limestone aggregate, 40 parts of marked wood simulated aggregate and SBS modified asphalt were preheated at 175℃ for three hours, and then the three were mixed at 180℃ to obtain a recycled asphalt mixture with wood simulation replacing new and old aggregates.

[0075] Unmarked wood simulated aggregate is used to simulate old aggregate; marked wood simulated aggregate is marked by drilling holes in the wood aggregate to simulate new aggregate.

[0076] Based on Example 1, the steps of the method for characterizing the degree of fusion of new and old asphalt based on fluorescence microscopy in this embodiment are as follows:

[0077] T1. Take out all unmarked wood simulated aggregates from the recycled asphalt mixture, place them on a glass slide, and observe the mixed asphalt on the surface of the wood simulated aggregate under a confocal microscope.

[0078] T2. Set the magnification of the microscope and adjust the position so that the mixed asphalt covers the entire viewing window. Start from the outermost layer of the wood simulated aggregate asphalt film and scan toward the innermost layer, with a total scanning depth of 20um. Set the scanning layer depth interval to 0.4um and output 51 fluorescence images of the old and new asphalt, recorded as the i=0, 1, 2, …, 50th layer fluorescence images, and the depth layers of the 51 fluorescence images are 0, 0.4, 0.8, 1.2 … 19.6, 20um, respectively.

[0079] T3. Perform noise reduction on the fluorescence image and calculate the average fluorescence intensity of each fluorescence image.

[0080] T4, the depth layer position 0um is SBS modified asphalt, that is, new asphalt. The fluorescence intensity of the fluorescence image at this position can be regarded as the new asphalt concentration of 1. The fluorescence intensities of the fluorescence images at other positions are normalized in turn to obtain the first average fluorescence intensity curve of the 0-20um asphalt film thickness layer.

[0081] T5. Use a confocal microscope to observe the 0-20um position on the surface of the wood simulated aggregate evenly coated with SBS modified asphalt, obtain the fluorescence image, calculate the average fluorescence intensity curve at the 0-20um depth position, and compare the fluorescence intensity curve with the average fluorescence intensity of the image at the 0um position to obtain the 0-20um fluorescence intensity signal attenuation, and calculate the attenuation correction function.

[0082] Table 1. Parameters at different layer cutting depths

[0083]

[0084]

[0085] T6. The concentration attenuation curve of the new asphalt is calculated from the fluorescence intensity change curve of the fluorescence image at the depth layer of 0 to 20 um. The influence of noise and the asphalt fusion layer are determined according to formula (5) and formula (6).

[0086] According to the usage ratio of new and old asphalt, that is, the number of old asphalt parts corresponding to 1 part of new asphalt during fusion, the entire asphalt film thickness layer is regarded as the fusion layer, and the degree of fusion of new and old asphalt DOB is calculated. * , the calculation formula is as follows,

[0087]

[0088] Where: min(,) means taking the smallest value of the elements in brackets, S virginrepresents the amount of new asphalt involved in fusion, S reclaimed Indicates the amount of old asphalt involved in fusion, C virgin Indicates the proportion of new asphalt added to the total amount of asphalt.

[0089] The overall degree of fusion of new and old asphalt DOB is obtained by integrating the thickness of the entire asphalt film. The calculation formula is as follows:

[0090]

[0091]

[0092]

[0093] In the formula, S virgin-i represents the new asphalt amount at the depth layer corresponding to the i=0th layer of fluorescence image, S reclaimed-i represents the amount of old asphalt in the depth layer corresponding to the i=0th layer of fluorescence image, C v-r represents the ratio of new and old asphalt, min(,) represents the smallest value of the elements in brackets, S virgin represents the amount of new asphalt involved in fusion, S reclaimed Indicates the amount of old asphalt involved in fusion, C virgin It indicates the proportion of new asphalt added to the total asphalt, W Rap;active Indicates the amount of old asphalt mobilized during the mixing process, W Rap;total Represents the total amount of old asphalt, RAP active,% It indicates the amount of active recycled asphalt mobilized during the mixing process, taken as 100%.

[0094] In this embodiment, the 0-10.4um layer is retained, and the fluorescence intensity curve is calculated after removing the influence of noise and fluorescence signal attenuation, the concentration curve of new asphalt in the fusion layer is determined, and the retained fluorescence intensity curve is corrected using the attenuation correction function to obtain the second average fluorescence intensity curve.

[0095] like Figure 5 As shown in the figure, the distribution map of new and old asphalt is obtained from the second average fluorescence intensity curve. During the fusion process of new and old asphalt, SBS modified asphalt gradually begins to diffuse into the aged asphalt layer, but the deeper it goes into the aged asphalt layer, the less SBS modified asphalt exists. In the fluorescence image obtained through the experiment, the fluorescence intensity is generated by the fluorescence effect of SBS modified asphalt. The fluorescence intensity curve generated after the image fluorescence intensity processing can represent the concentration of new asphalt in different layers. The phenomenon that the amount of SBS modified asphalt gradually decreases with the increase of longitudinal depth during fusion can be represented by the continuously decreasing SBS modified asphalt concentration curve.

[0096] T7. The distribution diagram of new and old asphalt can be obtained through the second average fluorescence intensity curve. The fusion degree formula can be used to calculate that the fusion degree of new and old asphalt on the old aggregate of the asphalt mixture with RAP content of 50% after mixing is 45.1%. This shows that the new and old asphalt cannot reach an ideal fusion state only through the mixing stage.

[0097] Example 3

[0098] In this embodiment, the recycled asphalt mixture in which wood simulates old aggregate is replaced is prepared by the provided materials and configuration method. The materials and configuration method are the same as those in Example 2.

[0099] Based on Examples 1 and 2, the steps of the method for characterizing the degree of fusion of new and old asphalt based on fluorescence microscopy in this embodiment are as follows:

[0100] T1. Take out all the marked wood simulated aggregates (simulated new aggregates) from the recycled asphalt mixture, place them on a glass slide, and observe the mixed asphalt on the surface of the wood simulated aggregates under a confocal microscope.

[0101] Steps T2 to T5 are the same as those in Example 2 and can be implemented with reference to them.

[0102] T6. The concentration attenuation curve of the new asphalt is calculated from the fluorescence intensity change curve of the fluorescence image of the 0-20um depth layer, and the influence of noise and the asphalt fusion layer are judged according to formula (5) and formula (6). The 0-8.4um layer is retained, and the fluorescence intensity curve is calculated after removing the influence of noise and fluorescence signal attenuation.

[0103] like Figure 6 As shown, the fluorescence curve of mixed asphalt on old aggregate has been analyzed in Example 2, and the fluorescence curve of mixed asphalt on new aggregate ( Figure 6 As shown in the bar graph, the fluorescence intensity at the depth layer after 8.4um is extremely small, and the difference with the fluorescence intensity at the depth layer from 0 to 8.4um is too large. It can be considered that there is no SBS modified asphalt after 8.4um, and the smaller fluorescence intensity is regarded as noise influence. Figure 6 Displayed in.

[0104] T7. According to the fusion degree formula, the fusion degree of new and old asphalt on new aggregates of asphalt mixture with RAP content of 50% and only mixed is 8.1%. This shows that the fusion degree of new and old asphalt on new aggregates and old aggregates in recycled mixtures is different. The fusion degree of new and old asphalt on new aggregates is smaller, mainly because only a small amount of new asphalt is distributed on new aggregates, which cannot effectively promote the fusion of new and old asphalt.

[0105] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for characterizing the degree of fusion of new and old asphalt based on fluorescence microscopy, characterized in that: The method for characterizing the degree of fusion of new and old asphalt comprises the following steps: S1. All wood simulated aggregates are taken out from the recycled asphalt mixture, placed on a glass slide, homogenized SBS modified asphalt is applied on the surface of the wood simulated aggregate, and the SBS modified asphalt on the surface of the wood simulated aggregate is observed under a confocal microscope, wherein the innermost layer of the asphalt film, the thickness layer of the asphalt film, and the surface layer of the asphalt film are sequentially arranged on the surface of the wood simulated aggregate from the inside to the outside; S2. Set the magnification of the microscope and adjust the position so that the mixed asphalt on the surface of the wood simulated aggregate covers the entire microscope window. Start from the surface layer of the asphalt film and scan toward the innermost layer of the asphalt film. Scan to cover the entire thickness layer depth of the asphalt film. Set the scanning layer depth interval and output n+1 new and old asphalt fluorescence images, which are recorded as the i=0, 1, 2, ..., nth layer fluorescence images respectively. When i=0, it corresponds to the surface layer of the asphalt film, and when i=n, ​​it corresponds to the innermost layer of the asphalt film. The i=0, 1, 2, ..., nth layer fluorescence images correspond to the fluorescence images of different layers respectively. S3, performing noise reduction processing on the fluorescence image, calculating the average fluorescence intensity of each fluorescence image and arranging them from the outside to the inside according to the scanning depth of the asphalt film of each fluorescence image, the depth layer corresponding to the i=0th layer of fluorescence image is 0um, and the depth of each layer of fluorescence image is defined in turn according to the scanning depth interval; S4, the position of the depth layer of 0um is taken as SBS modified asphalt, which is also called new asphalt, and the fluorescence intensity of the fluorescence image of the i=0th layer is regarded as the new asphalt concentration of 1, and the fluorescence intensity of the fluorescence image of the i=1, 2, ..., nth layer is normalized in turn to obtain the average fluorescence intensity curve in the normalized asphalt film thickness layer, which is recorded as the first average fluorescence intensity curve; S5. Conduct a set of control experiments, evenly apply homogeneous SBS modified asphalt on the surface of wooden aggregate, repeat steps S2-S3, obtain scanned images from layer 0 to layer n by confocal microscope scanning and obtain corresponding fluorescence intensities, which are recorded as the average fluorescence intensity curve of the control group, and compare the maximum fluorescence intensity of the fluorescence image of layer i=0 with the maximum fluorescence intensity of the fluorescence image of layer i=1, 2, ..., n in the asphalt film thickness layer to obtain the attenuation of the fluorescence intensity signal at each layer depth, and calculate the attenuation correction function; the calculation formula of the attenuation correction function in step S5 is as follows: Where: i represents the number of image layers distributed along the depth direction; k i represents the fluorescence intensity enhancement factor of the i-th layer image; represents the maximum fluorescence intensity of the i-th layer image after correction; x i represents the maximum fluorescence intensity of the i-th layer image; x max represents the maximum value of fluorescence intensity in all depth images; d i -d max represents the distance from the i-th image to the maximum fluorescence image along the depth direction; S6. Calculate the fluorescence intensity concentration attenuation change curve of the new asphalt using the first average fluorescence intensity curve, determine the influence of noise and the asphalt fusion layer, retain the layer with a fitting coefficient μ less than or equal to 95%, and calculate the fluorescence intensity concentration attenuation change curve after removing the influence of noise and fluorescence signal attenuation, and correct the retained fluorescence curve using the attenuation correction function to obtain the second average fluorescence intensity curve; the calculation formula of the fitting coefficient μ in step S6 is as follows: In the formula, ρ i represents the fluorescence intensity of the i-th layer fluorescence image, ρ max represents the maximum average fluorescence intensity in different layers of the entire asphalt film thickness layer, ρ min It indicates the minimum value of average fluorescence intensity in different layers of the entire asphalt film thickness layer; The formula of the fluorescence intensity ρ′ after removing the influence of noise and fluorescence signal attenuation in step S6 is as follows: In the formula, ρ′ represents the corrected fluorescence intensity, k is the fluorescence signal attenuation correction coefficient, ρ 噪声 It represents the fluorescence intensity generated by noise, which is the fluorescence intensity of the layer where the SBS modified asphalt stops longitudinal diffusion. max() means taking the maximum value from all the results in the brackets. S7. Perform fluorescence intensity concentration attenuation change analysis on the second average fluorescence intensity curve after removing noise and fluorescence signal attenuation by the area method to obtain the ratio of the amount of new and old asphalt in the asphalt film thickness layer, and calculate the fusion degree of the new and old asphalt according to the ratio of the amount; the calculation method of the fusion degree of the new and old asphalt in step S7 is as follows: According to the usage ratio of new and old asphalt, that is, the number of old asphalt parts corresponding to 1 part of new asphalt during fusion is fused, each layer of different depth is regarded as a fusion layer, and the degree of fusion of new and old asphalt in each layer of different depth is calculated. Then, the overall degree of fusion of new and old asphalt DOB is obtained by integrating the thickness of the entire asphalt film. The calculation formula is as follows: In the formula, S virgin-i represents the new asphalt amount at the depth layer corresponding to the i=0th layer of fluorescence image, S reclaimed-i represents the amount of old asphalt in the depth layer corresponding to the i=0th layer of fluorescence image, C v-r represents the ratio of new and old asphalt, min(,) represents the smallest value of the elements in brackets, S virgin represents the amount of new asphalt involved in fusion, S reclaimed Indicates the amount of old asphalt involved in fusion, C virgin It indicates the proportion of new asphalt added to the total asphalt, W Rap;active Indicates the amount of old asphalt mobilized during the mixing process, W Rap;total Represents the total amount of old asphalt, RAP active,% It indicates the amount of active recycled asphalt mobilized during the mixing process, taken as 100%.

2. The method for characterizing the degree of fusion of new and old asphalt based on fluorescence microscopy according to claim 1 is characterized in that: The calculation method of the fusion degree of the new and old asphalt in step S7 is as follows: According to the usage ratio of new and old asphalt, that is, the number of old asphalt corresponding to 1 part of new asphalt during fusion, the entire asphalt film thickness layer is regarded as the fusion layer, and the degree of fusion of new and old asphalt DOB is calculated. * , the calculation formula is as follows, Where: min(,) means taking the smallest value of the elements in brackets, S virgin represents the amount of new asphalt involved in fusion, S reclaimed Indicates the amount of old asphalt involved in fusion, C virgin Indicates the proportion of new asphalt added to the total amount of asphalt.

Citation Information

Patent Citations

  • Method for measuring mixing degree of new asphalt and old asphalt in thermal regeneration asphalt mixture

    CN111060463A

  • Method and system for determining fusion degree of recycled asphalt mixture

    CN111474157A

Cited By

  • Quantitative evaluation method for influence of old asphalt in hot recycled material on performance of hot recycled material

    CN117825671A